2000
DOI: 10.1021/ic000546m
|View full text |Cite
|
Sign up to set email alerts
|

Defining Chemical Species in Complex Environments Using K-Edge X-ray Absorption Spectroscopy:  Vanadium in Intact Blood Cells and Henze Solution from the TunicateAscidia ceratodes

Abstract: A K-edge X-ray absorption spectrum (XAS) fitting approach has been developed to speciate elements of interest in complex materials and used here to model the storage of biological vanadium within whole blood cells from the tunicate Ascidia ceratodes. The response of the K-edge XAS of solution-phase V(III) to increasing c(sulfate) at constant pH 1.8 produced specific and systematic effects in the preedge transition at 5468.8 eV (preedge transitions: 1s-->4A2 at 5464.9 +/- 0.1 eV, 1s-->4T2 at 5466.9 +/- 0.1 eV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
44
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 77 publications
6
44
0
Order By: Relevance
“…The XANES of these organisms, when compared to that of suitable model compounds, showed that the vanadium was predominantly in the V(3+) state in an octahedral environment, while the EXAFS revealed the nearest neighbours to be oxygens. In subsequent studies, the V XANES features were used to quantify the amounts of V(3+) ions associated with the biological catecholate-based chelator tunichrome, and water and sulphate, as well as mixtures of the latter in various species [114][115][116][117][118], and a detailed mechanism for the reduction of vanadate to V(3+) was proposed [119]. In this particular context, the role of sulphur in the vanadium metabolism was also investigated with sulphur K edge XANES [120][121][122].…”
Section: Biological Vanadium Accumulationmentioning
confidence: 99%
“…The XANES of these organisms, when compared to that of suitable model compounds, showed that the vanadium was predominantly in the V(3+) state in an octahedral environment, while the EXAFS revealed the nearest neighbours to be oxygens. In subsequent studies, the V XANES features were used to quantify the amounts of V(3+) ions associated with the biological catecholate-based chelator tunichrome, and water and sulphate, as well as mixtures of the latter in various species [114][115][116][117][118], and a detailed mechanism for the reduction of vanadate to V(3+) was proposed [119]. In this particular context, the role of sulphur in the vanadium metabolism was also investigated with sulphur K edge XANES [120][121][122].…”
Section: Biological Vanadium Accumulationmentioning
confidence: 99%
“…Each final spectrum represents the average of 16 to 20 individual scans. The vanadium K-edge XAS spectra of all the solid and solution models used herein have been reported previously [15,22,26,31,38].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…In contrast, incubation with DTT plus VO 2+ produced a significant new feature at 5469 eV in the vanadium K-edge XAS. This result proved consistently true in each of the three experiments.Both aqua vanadyl ion itself and sulfate ligation of V(III) produce intensity near 5469 eV in vanadium pre-K-edge XAS spectra [31]. However, the new 5469 eV feature stemming from the VO 2+ -incubated blood cells is far too intense to reflect changes in intravacuolar c sulfate , and thus indicates newly endocytosed vanadyl ion.…”
mentioning
confidence: 99%
See 2 more Smart Citations